An Existentialist Critique of Punishment - Logan, Nicholas (Stance: an international undergraduate philosophy journal, 2014)
In this paper, I provide an account of the way in which practices of punitive justice in the United States permanently foreclose the possibility of an open future for the punished. I argue that participation in a system where those forms of punishment are utilized is an act of bad faith because it involves the denial of the existential freedom of others as well as our own. Using Hannah Arendt’s account of Adolf Eichmann I show how such acts of bad faith are both natural modes of thought as well as inherently dangerous. Finally, I demonstrate that existentialism provides us with the ability to recreate our relationship to others and resist acts of bad faith, especially when it comes to crime and punishment.